SpiroTiger and KS Brief Stimulator: Specific Devices for Breathing and Well-Being in Post-COVID-19 Patients - Maria Chiara Parisi; Donatella Di Corrado; Omar Mingrino; Caterina Crescimanno; Federica Longo; Francesco Pegreffi; Vincenzo Cristian Francavilla (Journal of Functional Morphology and Kinesiology)
Background. Post-COVID-19 patients may develop impaired lung function, with reduced lung capacities and volumes, respiratory muscle weakness, and physical inactivity. The aim of this study was to determine the effects of a detailed protocol based on breathing training with two specifically designed respiratory devices (SpiroTiger and KS Brief Stimulator) in post-COVID-19 individuals. Methods. Sixteen young volunteers were randomly allocated into two groups: experimental (n = 8) and control (n = 8). The experimental group performed breathing training for 12 min two times a week for 9 months (from August 2023 to May 2024). Spirometric and baropodometric measurements were recorded every 3 months to evaluate the effects of the protocol. Results. Data analysis showed significant improvements in the forced vital capacity, peak expiratory flow indices, and postural parameters in the experimental group. Conclusions. In conclusion, based on the study findings, the specific breathing training protocol developed for post-COVID-19 patients has proven to be effective and significantly impacted the quality of breathing functions and the postural system.